Ground improvement using ground granulated blast-furnace slag (GGBS) and magnesium oxide - Wint, Su Lei (2017)
Numerous studies have been conducted to replace cement with sustainable materials such as Ground Granulated Blast-Furnace (GGBS) in soil improvement works. However, since GGBS has slow hydration process, the aid of hydrating agents such as reactive magnesia and lime are essential to achieve high early strength. This report hence aims to study the effect of reactive magnesia activated GGBS on weak soils by using unconfined compressive strength as a key engineering property. This report investigates the optimum MgO required to activate GGBS treated soil and analyses the effect of different compaction pressures on 28-day UCS strength. “Kaolin Clay Grade L2” was used as model soil and binder content added varied from 10% to 30%. MgO content of 5%, 10%, 15%, and 20% were added into the binder. The specimens were statically compacted by adopting “2-step compaction, reversal of loading face” method. It was found that the compressive strength generally increases as binder content increases. The optimum MgO content to achieve high early strength seemed to vary within a range of 10% to 20% depending on the binder content. It was also found that the impact of specimen compaction pressure was more significant in specimens with lower binder content. A cost analysis was also conducted to study the economy of MgO-GGBS mix over Portland cement and it appears that it is uneconomical to use high MgO content or high binder content. Two distinct failure patterns were observed, 45 to 60 degrees crack lines in weaker specimens and almost vertical fracture lines in stronger specimens.